2021
DOI: 10.1002/brb3.2061
|View full text |Cite
|
Sign up to set email alerts
|

New genetic prognostic biomarkers in primary central nervous system lymphoma (PCNSL)

Abstract: Background PCNSL is a rare extranodal NHL with poor prognosis. Tumorigenesis has been associated with hyperactivation of BCR downstream and NFkB pathways. We studied the prognosis of the relative expression profile of target genes of NFkB pathway (MYC, BCL2), the essential transcriptional regulator in hematopoiesis LMO2, the checkpoint regulation pathway MGMT, the transcription factor POU2F1, the immune checkpoint gene PDCD1, and the proto‐oncogene and transcriptional repressor gene BCL6 and its proteins in PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
(90 reference statements)
1
3
0
Order By: Relevance
“…Our study revealed that 86.5% of the patients had high Ki-67 expression (Ki-67 index > 50%), which is consistent with the literature and indicates rapid growth of tumor cells [12]. Reis et al [13] reported that increased expression of Bcl-6 in patients with PCNSL was associated with an extended period of survival, indicating its predictive value. Therefore, the lower expression of Bcl-6 in HIV-related PCNSL may indicate a poorer prognosis than in IC-PCNSL.…”
Section: Discussionsupporting
confidence: 90%
“…Our study revealed that 86.5% of the patients had high Ki-67 expression (Ki-67 index > 50%), which is consistent with the literature and indicates rapid growth of tumor cells [12]. Reis et al [13] reported that increased expression of Bcl-6 in patients with PCNSL was associated with an extended period of survival, indicating its predictive value. Therefore, the lower expression of Bcl-6 in HIV-related PCNSL may indicate a poorer prognosis than in IC-PCNSL.…”
Section: Discussionsupporting
confidence: 90%
“…The apoptosis pathway dysregulation in extranodal lymphomas is often due to abnormalities in key regulators like BCL2, p53, and MYC [ 45 47 ]. For example, upregulation of P53 may inhibit apoptosis in NKTCL [ 45 , 46 ].…”
Section: Signaling Pathways and Interventional Therapy In Extranodal ...mentioning
confidence: 99%
“…For example, upregulation of P53 may inhibit apoptosis in NKTCL [ 45 , 46 ]. Overexpression of MYC and BCL2 is frequently seen in patients with B-cell extranodal lymphomas [ 47 , 48 ] and PTCL [ 49 , 50 ]. BCL2 inhibitors like venetoclax [ 49 ] and obatoclax [ 50 ] can restore apoptosis.…”
Section: Signaling Pathways and Interventional Therapy In Extranodal ...mentioning
confidence: 99%
See 1 more Smart Citation